Differential behavioral responses of benthic and nektonic tadpoles to predation at varying water depths - de Souza, Yasmim Caroline Mossioli [UNESP]; Annibale, Fabiane Santana; Carvalheiro, Luísa Gigante; Vasconcelos, Tiago Silveira [UNESP]; Rossa-Feres, Denise de Cerqueira [UNESP] (Canadian Science Publishing, 2022)
Predators influence microhabitat selection and activity level of tadpoles, but it is still unclear how such responses to predators differ among species and how water column’s depth influences this predator–prey interaction. Here, we experimentally tested whether the presence of Odonata water nymphs influenced the spatial use and activity of benthic and nektonic tadpoles in different food availability contexts. Benthic tadpoles occupied and consumed more food at the bottom level, irrespective of predator’s presence. However, when predators were at the bottom, benthic tadpoles remained close to the cages, suggesting a typical “stay-still” defensive behavior known for Physalaemus nattereri (Steindachner, 1863). Nektonic tadpoles occupied shallower depths on predator presence, and they also consumed less food and avoided the predator by selecting food sources far from it. When the predator was at the bottom level and food was available, the distance of tadpoles to the cage tended to be smaller. Scinax fuscovarius (Lutz, 1925) tadpoles were more active when food was absent regardless of predator’s presence. When food was available, these tadpoles generally occupied and consumed more food at the bottom level. Tadpole responses depended not only on predator presence but also on a complex net of factors, which included tadpole habit, antipredatory behavior, and availability and location of food.
Keywords: feeding behavior; induced defenses; Micrathyria sp; niche occupancy; Physalaemus nattereri; Scinax fuscovarius; swimming activity